2013 IEEE China Summit and International Conference on Signal and Information Processing 2013
DOI: 10.1109/chinasip.2013.6625313
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic modeling with rich syntactic context in HMM-based Mandarin speech synthesis

Abstract: To further explore the relevance between prosody and syntax information, we propose a novel approach of prosodic modeling with rich syntactic context instead of prosodic structure in HMM-based Mandarin speech synthesis. Considering the characteristics of Mandarin itself, word-based and characterbased syntactic parsings are investigated in this study respectively. This method can not only avoid the existing cascade error in conventional way of prosodic parameter prediction but also not rely on the manually anno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…A development set of 500 sentences is required to adjust the parameters. The possible values of low threshold are set to be (3,4,5,6), and the possible values of up thresholds are (7,8,9,10). On the development set, the best performance was obtained when low threshold and up threshold were 4 and 8 respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A development set of 500 sentences is required to adjust the parameters. The possible values of low threshold are set to be (3,4,5,6), and the possible values of up thresholds are (7,8,9,10). On the development set, the best performance was obtained when low threshold and up threshold were 4 and 8 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the level information of a word in the syntactic tree is one of the best five features for predicting prosodic phrase boundaries. The authors of [8] demonstrated that the syntactic structure information was able to significantly improve the duration generation in a speech synthesis system. Zhang et al noticed that the prosodic structure of a sentence is also a tree, and they proposed a method of converting a syntactic tree to a prosodic tree [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the silence between VP and NP is usually longer than the break between NP and NP. Researches also implied that longer duration of break often occurred at the boundary with higher level syntactic phrase [24].…”
Section: Syntactic Phrase and Dependence Featuresmentioning
confidence: 95%
“…The phrase types have been proven related to break level many years ago [16]. For example, the length of break between VP and NP is always longer than the break between NP and NP.…”
Section: Syntactic Phrase Featuresmentioning
confidence: 99%